Цель оправдывает средства: [рассказы] / Евгений Монах - Монах Евгений Михайлович (Бандитский роман, 2002)
Экземпляры: ф.10 (2003) / Инвентарный номер: 47340 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: М 77 / ГРНТИ: 17.82.32 / ББК: 84(2Рос=Рус)6-44